The Influence of Organizational Behavior, Business Partnership, and Motivation on The Performance of Micro and Small Businesses in Sleman Regency - Titi Laras; Fathonah Eka Susanti; Sri Wara Nusandari; Kholifah Fil Ardhi (Pusat P2M Politeknik Negeri Batam, 2021)
This research is aimed to find out the influence of organizational behavior, business partnerships and motivation on the performance of micro and small businesses in Sleman Regency. The research is conducted in “ Forum Komunikasi Usaha Mikro, Kecil dan Menengah” in Sleman Regency. This is quantitative research with a sample of 102 micro and small entreprises in Sleman Regency. The data analysis is done with SPSS with multiple linear regression analysis at the significance level α = 0.05. The results shows that either partially or simultaneously organizational behavior, business partnership and motivation have positive influences and are significant to business performance. The influence of organizational behavior, business partnership and motivation on business performance is the performance of micro and small businesse is indicated by Adjusted R Square of 55.1%.